Fast Algorithms for Orthogonal and Biorthogonal Modulated Lapped Transforms - Malvar, Henrique S. (Institute of Electrical and Electronics Engineers, Inc., 1998)
New algorithms for the computation of orthogonal and biorthogonal modulated lapped transforms(MLTs) are presented. The new structures are obtained by combining the MLT window operators with stages from a previously introduced structure for the type-IV discrete cosine transform (DCT-IV). The net result is fewer multiplications and additions than previously reported algorithms. For the orthogonal MLT, in particular, the new structure requires the computation of a slightly modified DCT-IV and some extra additions, but no further multiplications; so it demonstrates that the multiplicative complexity of the orthogonal MLT is the same as that of the DCT-IV.
Twelfth Conference on Uncertainty in Artificial Intelligence (UAI1996)